Environmental Taxation and Food Security in Sub-Saharan Africa: Does Information and Communications Technology Penetration Matter? - Okere, Wisdom; Ambe, Cosmas (International Journal of Economics and Financial Issues, 2025)
This study examines the mediating role of information and communications technology in the relationship between environmental tax and food security across 15 sub-Saharan African countries from 2006 to 2024. Based on the Digital Development Theory and supported by the Environmental Kuznets Curve Theory, the research utilised the panel autoregressive distributed lag model, fully modified ordinary least squares, and mediation analysis to address the research objectives. The results showed that environmental tax significantly improves food security in the long term. Additionally, ICT not only enhances food availability and accessibility but also mediates the effects of green tax policies. The interaction between ICT and environmental tax further boosts food security outcomes, illustrating that digitalisation is a vital driver of fiscal environmental interventions. This research offers empirical evidence for integrated and environmental policy reforms and advances the theoretical understanding of how digital development and green taxation collectively support food systems in emerging nations.